Evaluation and management of traumatic pneumothorax: A Western Trauma Association critical decisions algorithm. Issue 1 (January 2022) - de Moya, Marc; Brasel, Karen J.; Brown, Carlos V.R.; Hartwell, Jennifer L.; Inaba, Kenji; Ley, Eric J.; Moore, Ernest E.; Peck, Kimberly A.; Rizzo, Anne G.; Rosen, Nelson G.; Sperry, Jason; Weinberg, Jordan A.; et al.
Abstract : ABSTRACT: This is a recommended algorithm of the Western Trauma Association for the management of a traumatic pneumothorax. The current algorithm and recommendations are based on available published prospective cohort, observational, and retrospective studies and the expert opinion of the Western Trauma Association members. The algorithm and accompanying text represents a safe and reasonable approach to this common problem. We recognize that there may be variability in decision making, local resources, institutional consensus, and patient-specific factors that may require deviation from the algorithm presented. This annotated algorithm is meant to serve as a basis from which protocols at individual institutions can be developed or serve as a quick bedside reference for clinicians. LEVEL OF EVIDENCE: Consensus algorithm from the Western Trauma Association, Level V.